Investigation of the spongillid Spongilla alba Carter, 1849 reveals a new group of brackish-water sponges. Issue 8 (17th November 2021) - Sokolova, Agniya M.; Palatov, Dmitry M.; Masuda, Yoshiki; Itskovich, Valeria B.
Abstract : Freshwater sponges are widely distributed throughout the world, but their taxonomy and phylogenetics remain obscure. Studying distantly located specimens of the cosmopolitan spongillid Spongilla alba Carter, 1849, we revealed that these sponges differ from the rest of the studied Spongilla specimens by ITS1, ITS2, and COI sequences. Morphotraits of the sponges have a remarkable peculiarity compared with Spongilla genus: slightly fusiform slender microscleres with complex spines arranged in a pedunculate rosette at the middle and simple spines at the tips. Given both genetic and morphological differences, these sponges deserve being assigned to a new genus, Rosulaspongilla gen. nov. We found this genus to comprise two species that significantly differ in ITS sequences and have peculiarities in morphotraits. These sponges clearly prefer slightly brackish water, which highlights their independent status. Our result stresses the need to use an integrative approach in the investigation of freshwater sponges. http://zoobank.org/urn:lsid:zoobank:org:pub:2B0A7FC0-35D7-474C-819E-2FE8D49B9B21